Frequency of coronary artery anomalies and relationship between coronary artery with anomalous origin and myocardial bridge - Bektas Murat; Selda Murat (Medicine Science, 2020)
The association between coronary artery with anomalous origin and myocardial bridge is not investigated well yet. We aimed to investigate the incidence of coronary artery anomalies and the relationship between coronary artery with anomalous origin and the presence of myocardial bridge. The coronary angiography records of 6100 patients who undergone coronary angiography in Eskisehir Osmangazi University school of medicine hospital between 2008 and 2010 were retrospectively assessed. The Angelini classification system was used to classify the coronary artery anomalies. Coronary arteries were classified in three classes: (i) Coronary artery with anomalous origin, (ii) abnormal course (myocardial bridge) and; (iii) termination (fistula). Myocardial bridge is a type of coronary anomaly and is defined as the case where a segment of the epicardial coronary artery is covered by myocardium. The incidence of coronary artery anomalies was 3.1%. Coronary artery with anomalous origin was 1.5%, myocardial bridge was 1.4% and fistula was 0.3%. The frequency of coronary artery anomalies was significantly higher in males (66.7%) than in females (33.3%). Among the coronary arteries with anomalous origin, the circumflex and left descending artery originating from separate ostia in the left aortic sinus was the most common anomaly. Myocardial bridge was significantly higher in males (81.9%) than in females (18.07%). Among the coronary artery with anomalous origin, originating of right coronary artery from left sinus of valsalva was significantly higher with the presence of myocardial bridge (p [Med-Science 2020; 9(3.000): 595-599]